2008
DOI: 10.1183/09031936.00165207
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in physiological progression of idiopathic pulmonary fibrosis

Abstract: In idiopathic pulmonary fibrosis, incidence is higher in males, and females may have better survival. The aim of the present study was to determine whether the rate of increase in desaturation during serial 6-min walk testing would be greater, and survival worse, for males versus females.Serial changes in the percentage of maximum desaturation area (DA) over 1 yr were estimated using mixed models in 215 patients. DA was defined as the total area above the curve created using desaturation percentage values obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
37
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(50 citation statements)
references
References 29 publications
(30 reference statements)
11
37
1
1
Order By: Relevance
“…A study of 215 patients that examined gender differences in IPF found that female sex conferred a significant survival advantage over male sex (HR 0.63; CI 0.41e0.97) after adjusting for age, smoking history, DL CO , and maximum desaturation area [46].…”
Section: Male Sexmentioning
confidence: 99%
“…A study of 215 patients that examined gender differences in IPF found that female sex conferred a significant survival advantage over male sex (HR 0.63; CI 0.41e0.97) after adjusting for age, smoking history, DL CO , and maximum desaturation area [46].…”
Section: Male Sexmentioning
confidence: 99%
“…Two studies also assessed the association of 6MWD with hospitalisation and both of them (100%) found statistically significant associations [109,120]. In patients with ILD, four (50%) out of eight studies found statistically significant associations of 6MWD with mortality (table S24) [69,[123][124][125][126][127][128][129]. Six (66%) out of nine studies in patients with pulmonary hypertension found statistically significant associations of 6MWD with mortality (table S25) [43,[130][131][132][133][134][135][136][137].…”
Section: Relationship Of 6mwd To Clinical Outcomesmentioning
confidence: 99%
“…14 studies included patients with COPD [109][110][111][112][113][114][115][116][117][118][119][120][121][122], eight studies included patients with ILD [69,[123][124][125][126][127][128][129], nine studies included patients with PAH [43,[130][131][132][133][134][135][136][137] and four included studies patients with other chronic respiratory disease or on the list for transplantation [138][139][140][141]. Average 6MWD at baseline was between 300 and 450 m ( fig.…”
Section: Relationship Of 6mwd To Clinical Outcomesmentioning
confidence: 99%
“…In their study, walk distance was a better predictor of prognosis than FVC. Lama et al , in a smaller study containing 83 patients with IPF, found that desaturation below 88% at any time during a 6-min walk test was predictive of a poorer outcome [52] , an effect that Han et al have shown to be more pronounced in males than females [53] .…”
Section: Physiology Datamentioning
confidence: 97%